2010
DOI: 10.1111/j.1349-7006.2010.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of intraperitoneally administrated paclitaxel nanoparticles solubilized with poly (2‐methacryloxyethyl phosphorylcholine‐co n‐butyl methacrylate) in peritoneal metastatic nodules

Abstract: Intraperitoneal (i.p.) administration of paclitaxel nanoparticles (PTX‐30W) prepared by solubulization with the amphiphilic copolymer of 2‐methacryloxyethyl phosphorylcholine and n‐butyl methacrylate can efficiently suppress the growth of peritoneal metastasis. In this study, we characterized the drug distribution of i.p. injected PTX‐30W in peritoneal tumor and liver in a mouse model using MKN45, human gastric cancer cells. Oregon green‐conjugated PTX‐30W showed perivascular accumulation in MKN45 tumor in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 28 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…The IP‐administered anticancer drug directly exposes the disseminated cancer nodules in the peritoneal cavity to drug infiltration . We demonstrated in a mouse model that IP‐administered PTX infiltrates approximately at least 100 to 200 μm from the surface of the disseminated tumor within 24 hours . In contrast, even if anticancer drugs are IV administered, most of them cannot cross the peritoneum–serum barrier and, therefore, cannot adequately reach the disseminated nodule …”
Section: Discussionmentioning
confidence: 98%
“…The IP‐administered anticancer drug directly exposes the disseminated cancer nodules in the peritoneal cavity to drug infiltration . We demonstrated in a mouse model that IP‐administered PTX infiltrates approximately at least 100 to 200 μm from the surface of the disseminated tumor within 24 hours . In contrast, even if anticancer drugs are IV administered, most of them cannot cross the peritoneum–serum barrier and, therefore, cannot adequately reach the disseminated nodule …”
Section: Discussionmentioning
confidence: 98%
“…ABX is used for treating patients with breast, lung, and pancreatic cancers, and is undergoing clinical evaluation for IP treatment of advanced cancer in the peritoneal cavity. Compared to free anticancer drugs, IP administered nano-formulated drugs have superior antitumor activity in PC (711). Nanoparticles can be loaded with poorly soluble hydrophobic anticancer drugs, allowing for higher tumor drug exposure for sustained antitumor activity and enhanced tumor penetration.…”
Section: Introductionmentioning
confidence: 99%
“…Our long‐term goal is to enhance radiation therapy efficacy by using imaging agents and radiosensitizers to deliver and concentrate the radiation in the tumor areas. Recent studies showed improved therapeutic outcomes when NPs are injected directly via the IP route compared to IV injection . With this method, NPs are retained in the peritoneal cavity and, thus, have more opportunity to target tumor masses.…”
Section: Resultsmentioning
confidence: 99%